Technical efficiency of Nigerian insurance companies: a data envelopment analysis and patent growth curve modelling approach - Jaiyeoba, Haruna Babatunde; Haron, Razali (International Journal of Data Envelopment Analysis, 2015)
The main purpose of this paper is to investigate the performance of Nigerian insurance companies using Data Envelopment Analysis (DEA). Because of the unavailability of the required data, the study is limited to ten Nigerian insurance companies for the period of five years from 2008 to 2012. The input employed were commission expenses and management expenses, while premium and investment income were used as the output. Data were sourced from the respective insurance websites and African financial websites. DEA was the main methodology used in analyzing the data of this study while ratio analysis (liquid asset to total asset, total equity to total asset and return on asset) was also used in addition to the DEA. The overall result of the Total Factor Productivity (TFP) shows that Nigerian insurance industry is less efficient and this is caused by low level of Technical efficiency (EF) change including Technological change (TECH); this is also confirmed by the result of Latent Growth Curve Modeling (LGCM) which reveals that their efficiency over the period was declining. However, some of the leading insurance companies in terms of performance (TFP) are Leadway insurance, Standard Alliance insurance and Sovereign Trust insurance, among the insurance firms. The results of the ratio on the other hand reveal that Leadway is the highest in terms of profitability, Aiico was more liquid compared to the other firms and Oasis insurance finances more of its asset with shareholder’s fund compared to other insurance firms.